Synthesis and Characterization of Transition Metal Complexes with 2,2’-[(Propylene-1,3-diyldioxy)bis(nitrilomethylidyne)]diphenol - Chai, Feng-Ying; Zhang, Xin-Ying; Zhao, Meng-Meng; Wang, Zheng-Kun; Meng, Jiao-Long; Zhang, Li-Sha; Wang, Ke-Tai (Asian Journal of Chemistry, 2013)
In anhydrous ethanol medium, a series of transition metal complexes have been synthesized by the reaction of 2,2'-[(propylene-1,3-diyldioxy)bis(nitrilomethylidyne)]diphenol (H2L) with Cu(II), Ni(II), Co(II) and Mn(II) acetate hydrate. All these metal complexes were characterized by elemental analyses, IR spectra, UV-VIS spectra, molar conductances and TG-DTA analyses.